1989
DOI: 10.1128/aac.33.11.1878
|View full text |Cite
|
Sign up to set email alerts
|

In vitro activities and targets of three cephem antibiotics against Haemophilus influenzae

Abstract: The antimicrobial activities of cefixime, cefpodoxime, and ceftibuten were determined with 18 ampicillinsusceptible (Amp'), 13 ampicillin-resistant P-lactamase-producing (AmprBLP), and 7 ampiciln-resistant non-j-lactamase-producing (AmprNBLP) strains of Haemophilus influenzae. An effect of inoculum density on apparent MIC, the bactericidal activity of these agents, and the targets of the three cephems were determined. The MICs of cefixime, cefpodoxime, and ceftibuten for 90% of the Amps and Amp%BLP isolates we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
6
1

Year Published

1990
1990
1994
1994

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 27 publications
(8 citation statements)
references
References 22 publications
1
6
1
Order By: Relevance
“…Recently, we used HTM to compare the in vitro susceptibility of H. influenzae to three cephem antibiotics (6). In that study, we observed that the ampicillin MICs with HTM were lower for AmprNBLP strains compared with our previous data obtained with the same isolates in our laboratory when we used supplemented brain heart infusion medium (sBHI; Difco Laboratories, Detroit, Mich.); those data prompted this investigation.…”
contrasting
confidence: 35%
“…Recently, we used HTM to compare the in vitro susceptibility of H. influenzae to three cephem antibiotics (6). In that study, we observed that the ampicillin MICs with HTM were lower for AmprNBLP strains compared with our previous data obtained with the same isolates in our laboratory when we used supplemented brain heart infusion medium (sBHI; Difco Laboratories, Detroit, Mich.); those data prompted this investigation.…”
contrasting
confidence: 35%
“…Our cefixime MICqq value of 0.12 pg/ml for Haemophilus strains are consistent with those reported by Powell and Williams [12] in AMPs and AMPr BLP strains and with the data pub lished by other authors (8,13].…”
Section: Discussionsupporting
confidence: 81%
“…Such ampicillin-resistant, 3-lactamasenonproducing (Ampr NBLP) strains probably represent <1% of all H. influenzae isolates recovered in the United States (4, 9, 18), but they are becoming more prevalent in the United Kingdom (19). Ampr NBLP strains are thought to have altered penicillin-binding proteins with decreased affinities for ampicillin and other ,-lactams (13,14,18 (2,3,8,16,17). Interpretive criteria for microdilution tests and disk diffusion tests were those described in the current National Committee for Clinical Laboratory Standards documents (16,17).…”
mentioning
confidence: 99%